ابو انیس محمد برکت علی لودھیانوی کی صو فیانہ نثرMystical Prose of Abu Anees Muhammad Barkat Ali Ludhianawi (Al-Qamar, 2021)
Abu Anees Muhammad Barkat Ali  Ludhianwi (1911-1997) is a well-known intellectual, literary and spiritual figure of present era. His research and creative books are of international fame. In terms of research and compilation, his books “Kitab-Ul-Amal Bis- Sunnah Al-Ma’roof Tarteeb Sharif”and “Asma Ul Nabi-ul-Kareem” are considered as textbooks and reference books in the universities of Islamic countries. His work in  rdu Prose “Maqalat-e”-Hikmat  (30 volumes) is a unique example in terms of thickness, style of expression and intellectual themes. The article under study titled “Abu Anees Muhammad Barkat Ali Ludhianwi’s Mystical Prose” has been  written in the light of the references of the same book. Hazrat Abu Anees is a practicing Sufi. In his writings, he presents the mystic thoughts in the light of Quran and Sunnah. According to him, Sufisim and monasticism are the practical names of the teachings of the Quran and Sunnah. His style is a fine example of eloquence. He explains his thoughts and ideas in an understandable way simplicity, smoothness, comprehensiveness and brevity.
Keywords: Barkat Ali Ludhianwi; Maqalat-e-Hikmat; Intellectual; creative compilation; eloquence; simplicity; comprehensiveness